PENGARUH SERVANT LEADERSHIP TERHADAP FIRM PERFORMANCE DENGAN ABSORPTIVE CAPACITY DAN READINESS TO CHANGE SEBAGAI VARIABEL MEDIASI - Gilang Trio cahyono; Sidiq Permono Nugroho (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
The purpose of this study is to analyse the effect of servant leadership on firm performance with absorptive capacity and readiness to change as mediating variables. This research method is quantitative research. The data collection method that will be used in this study uses a questionnaire. In this study, researchers used a Likert scale as a research instrument. The population to be used in this study is Manufacturing Companies in the Wates Yogyakarta area. The sample of this study was 210 respondents. The sampling technique used in this research is non probability sampling technique. The data analysis technique used in this research is Smart Partial Least Square (PLS). The results of this study are that Servant Leadership has a significant effect on Absorptive Capacity. Servant Leadership has no significant effect on Firm Performance. Servant Leadership has a significant effect on Readiness to Change. Absorptive Capacity has a significant effect on Firm Performance. Readiness to Change has a significant effect on Firm Performance. Absorptive Capacity mediates the effect of Servant Leadership on Firm Performance. Readiness to Change mediates the effect of Servant Leadership on Firm Performance.